Activation and memory differentiation of total and HIV-specific T cells that associate with viral control during subtype C HIV-1 infection - Maenetje, Pholo Wilson (My University, 2014)
The development of an effective HIV-1 vaccine is critical in mitigating the global HIV epidemic. Understanding the interplay between host immune functions, such as cellular memory differentiation, activation, inflammatory cytokine production and the virus, may provide key insight into anti-HIV immunity that can inform vaccine development. This PhD aims at understanding and identifying T cell memory, functional profiles and the effect of immune activation on in vivo HIV-1 control during primary/early infection. Furthermore, this study aims to examine and understand the potential mechanisms related to immune activation during primary HIV-1 infection. Use was made of a unique cohort of individuals recruited during primary HIV-1 infection and using a battery of assays to characterize and identify properties and mechanisms of T cell reactivity and activation. Multiparameter flow cytometry was used to measure memory differentiation (CD27 and CD45RO), activation (CD38, HLA-DR), proliferation (Ki67), and multiple cellular functions (CD107, IFNγ, IL-2, MIP-1β and TNFα) of total and antigen-specific CD4+ and CD8+ T cells from 15 HIV-1 and CMV-coinfected individuals followed over 15 months of HIV-1 infection. Plasma samples were used to measure markers associated with intestinal permeability (LBP, sCD14, I-FABP and IgM EndoCAb) and inflammation (IL-1β, IL-6, IL-7, IL-10, IL-12p70, TNFα and MCP-1). The differentiation profile of HIV-Gag specific memory CD4+ and CD8+ T cells was found to be mainly characterized by an early differentiated (ED) memory phenotype relative to CMV- specific CD4+ and CD8+ T cells. Moreover, the proportion of HIV-specific ED-memory CD4+ T cells inversely associated with viraemia, suggesting that HIV-1 antigen burden could be shaping the differentiation of HIV-specific memory CD4+ T cells during primary infection. Primary HIV-1 infection was also characterized by significantly elevated levels of activated and proliferating total and HIV-specific memory CD4+ and CD8+ T cells, which positively correlated with viraemia. Furthermore, upon sorting of total activated memory CD4+ T cells, these cells harboured more gag provirus DNA than non-activated memory cells, suggesting that activated memory CD4+ T cells support ongoing HIV-1 replication. When examining the relationship between memory differentiation and activation markers, the level of T cell activation was equally expanded across the different memory CD4+ T cell subpopulations, suggesting that memory differentiation of CD4+ T cells was unlikely driven per se by the level of T cell activation. In addition, when teasing out events that may result in T cell activation during primary HIV-1 infection using statistical models, plasma markers of microbial translocation and inflammation were found to correlate with immune activation. The lack of these associations in HIV-uninfected controls suggests that microbial translocation and inflammation were unlikely causative. Analysis of the polyfunctional profile of memory T cells during primary HIV-1 infection showed that HIV-specific CD4+ and CD8+ T cell responses are less polyfunctional relative to CMV-specific memory CD4+ and CD8+ T cell responses. Furthermore, the polyfunctional status of HIV-specific CD4+ T cells significantly correlated with viraemia at 3 months post-infection, indicating that the polyfunctionality of memory CD4+ T cells is likely driven by HIV-1 antigenemia. Overall, these observations suggest that HIV-1 antigenic burden appears to be a central driver of memory differentiation, activation/inflammation and polyfunctionality of T cells. Given the impact of HIV-1 viraemia on immune activation and memory T cell dysfunction (as measured by limited polyfunctional HIV-specific responses), preventing high levels of viral replication, with a vaccine or other early interventions may serve as an important strategy for delaying HIV-1 disease progression.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Health Sciences, 2012.
Keywords: HIV-1 Infections